Near‐Infrared Ternary Tandem Solar Cells. Issue 45 (1st October 2018) - Li, Yongxi; Lin, Jiu‐Dong; Liu, Xiao; Qu, Yue; Wu, Fu‐Peng; Liu, Feng; Jiang, Zuo‐Quan; Forrest, Stephen R.
Abstract: The paucity of near‐infrared (NIR) organic materials with high absorption at long wavelengths, combined with large diffusion lengths and charge mobilities, is an impediment to progress in achieving high‐efficiency organic tandem solar cells. Here a subcell is employed within a series tandem stack that comprises a solution‐processed ternary blend of two NIR‐absorbing nonfullerene acceptors and a polymer donor combined with a small‐molecular‐weight, short‐wavelength fullerene‐based subcell grown by vacuum thermal evaporation. The ternary cell achieves a power conversion efficiency of 12.6 ± 0.3% with a short‐circuit current of 25.5 ± 0.3 mA cm −2, an open‐circuit voltage of 0.69 ± 0.01 V, and a fill factor of 0.71 ± 0.01 under 1 sun, AM 1.5G spectral illumination. The success of this device is a result of the nearly identical offset energies between the lowest unoccupied molecular orbitals (LUMOs) of the donors with the highest occupied molecular orbital (HOMO) of the acceptor, resulting in a high open‐circuit voltage. A tandem structure with an antireflection coating combining these subcells demonstrates a power conversion efficiency of 15.4 ± 0.3%. Abstract : A tandem organic photovoltaic cell combining a nonfullerene‐acceptor‐based ternary cell with a fullerene small‐molecule binary subcell is reported. The cell combines vacuum‐ and solution‐deposited layers, achieving a power conversion efficiency of 15.4%.